Blurred vision for Bausch & Lomb - Curry, Joe; Ratliff, Julie; ORourke, James S. (London : SAGE Publications Ltd, 2017)
On March 3, 2006, Bausch & Lomb received a phone call from New Jersey ophthalmologist Dr. David S. Chu regarding three patients afflicted with a serious fungal condition known as fusarium keratitus. These patients all were contact-lens wearers, and had used Bausch & Lombs ReNu with MoistureLoc lens solution. This telephone call started a chain of events, accusations, and CDC investigations that eventually led to a recall by Bausch & Lomb in the U.S. and overseas, but not before the crisis had threatened to damage not only sales of its popular lens solution, but also Bausch & Lombs reputation.
Originally published: Curry, J., Ratliff, J., & ORourke, J. S. (2006). Blurred vision for Bausch & Lomb. 06-16. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bausch & Lomb, Inc. -- Public opinion; Contact lens industry -- Safety measures; Microbial contamination; Oculomycoses; Corporate image